Development of a Periprocedure Trigger for Outpatient Interventional Radiology Procedures in the Veterans Health Administration. Issue 3 (25th April 2023) - Bart, Nina; Mull, Hillary J.; Higgins, Mikhail; Sturgeon, Daniel; Hederstedt, Kierstin; Lamkin, Rebecca; Sullivan, Brian; Branch-Elliman, Westyn; Foster, Marva
Abstract : Objectives: Interventional radiology (IR) is the newest medical specialty. However, it lacks robust quality assurance metrics, including adverse event (AE) surveillance tools. Considering the high frequency of outpatient care provided by IR, automated electronic triggers offer a potential catalyst to support accurate retrospective AE detection. Methods: We programmed previously validated AE triggers (admission, emergency visit, or death up to 14 days after procedure) for elective, outpatient IR procedures performed in Veterans Health Administration surgical facilities between fiscal years 2017 and 2019. We then developed a text-based algorithm to detect AEs that explicitly occurred in the periprocedure time frame: before, during, and shortly after the IR procedure. Guided by the literature and clinical expertise, we generated clinical note keywords and text strings to flag cases with high potential for periprocedure AEs. Flagged cases underwent targeted chart review to measure criterion validity (i.e., the positive predictive value), to confirm AE occurrence, and to characterize the event. Results: Among 135, 285 elective outpatient IR procedures, the periprocedure algorithm flagged 245 cases (0.18%); 138 of these had ≥1 AE, yielding a positive predictive value of 56% (95% confidence interval, 50%–62%). The previously developed triggers for admission, emergency visit, or death in 14 days flagged 119 of the 138 procedures with AEs (73%). Among the 43 AEs detected exclusively by the periprocedure trigger were allergic reactions, adverse drug events, ischemic events, bleeding events requiring blood transfusions, and cardiac arrest requiring cardiopulmonary resuscitation. Conclusions: The periprocedure trigger performed well on IR outpatient procedures and offers a complement to other electronic triggers developed for outpatient AE surveillance.